Simple and complex pig starters compared - B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1969)
Baby pigs have the ability to grow rapidly and efficiently. Creep rations at an early age enhance their potential. Most commercial creep rations contain feedstuffs to increase palatability and acceptability. Are these ingredients necessary or will rather simple starters produce similar gains? Five starters were compared, varying from a simple corn-milo- soybean meal ration to a ration containing several palatability aiding ingredients–from 10 days of age to weaning at 28-35 days; and from 6 weeks to 10 weeks of age.; Swine Day, Manhattan, KS, September 25, 1969
Keywords: Swine day; 1969; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 151; Swine; Creep rations; Palatability